2002
DOI: 10.1111/1467-9426.00247
|View full text |Cite
|
Sign up to set email alerts
|

The Common European Economic Space Between Russia and the EU: an Institutional Anchor for Accelerating Russian Reform

Abstract: The prospect of bringing the European Union and Russia closer together within a Common European Economic Space (CEES) tops the agenda in the EU-Russia dialogue, confirming that the EU views Russia as a strategic partner. 1 This article argues that the CEES is not only positive for Russian economic growth, but that it is a condition for acceleration of sustainable growth and higher productivity in Russia. The aim of the EU in building the CEES is not to force Russia into a particular mould, but to offer a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The free trade agreement of 1972 and the Bilateral agreements of 1999 gives Switzerland special status within the EU (Dupont and Sciarini, 2001). The Common European Economic Space (CEES) affirms the EU's view of Russia as a strategic partner 2 (Samson, 2008). Goldthau and Sitter (2015) (page 942) described this trend as "come and play on the EU's turf and accept its rules as the price for access, or when neighboring states voluntarily choose to adopt EU rules and regulations as their own".…”
Section: Sample Selection and Data Extractionmentioning
confidence: 98%
See 1 more Smart Citation
“…The free trade agreement of 1972 and the Bilateral agreements of 1999 gives Switzerland special status within the EU (Dupont and Sciarini, 2001). The Common European Economic Space (CEES) affirms the EU's view of Russia as a strategic partner 2 (Samson, 2008). Goldthau and Sitter (2015) (page 942) described this trend as "come and play on the EU's turf and accept its rules as the price for access, or when neighboring states voluntarily choose to adopt EU rules and regulations as their own".…”
Section: Sample Selection and Data Extractionmentioning
confidence: 98%
“…We choose a geographical approach because continental European countries have close involvement concerning trade, business, and investment. In many cases, non-EU members but continental European companies follow EU laws and directives to continue business operations, facilitating import, export and investment within the continent (Dupont and Sciarini, 2001;Samson, 2008;Emerson and Woolcock, 2002). For example, The European Economic Area (EEA) brings Norway as a partner of EU member states (Emerson and Woolcock, 2002).…”
Section: Sample Selection and Data Extractionmentioning
confidence: 99%
“…In these Models 18–20 (Table 10), we examined the impact of interaction – IQ and economic growth – on companies’ sustainability and FP in the European context. Previous literature has demonstrated that these two interactional variables play an important role on the macro interorganizational environment when they interact (Butkiewicz and Yanikkaya, 2006; Salman et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The free trade agreement grants Switzerland a privileged status within the EU (Dupont and Sciarini, 2001). The Common European Economic Space confirms the EU's position of Russia as a strategic partner [1] (Samson, 2008). This phenomenon was described by Goldthau and Sitter (2015), as paying the price to get access to the EU market when neighboring states voluntarily choose to adopt EU rules and regulations as their own.…”
Section: Sample Selection and Data Extractionmentioning
confidence: 96%
See 1 more Smart Citation